Localised delivery of interleukin-13 from a PLGA microparticle embedded GelMA hydrogel improves functional and histopathological recovery in a mouse contusion spinal cord injury model - Ciara M. Walsh; Ruth Colbert; James P. Reynolds; Emily Dunne; Emmanuelle D. Aiyegbusi; Ross O'Carroll; Jacek K. Wychowaniec; Takahiro Masuda; Klaus-Peter Knobeloch; Marco Prinz; Dermot F. Brougham; Dearbhaile Dooley (Bioactive Materials)
Spinal cord injury (SCI) is a severe neurological condition with limited regenerative capacity and no effective curative treatments. Interleukin-13 (IL-13), an immunomodulatory cytokine, has shown therapeutic potential by promoting alternative immune activation and improving recovery after SCI in mice. However, cell-based IL-13 delivery is hindered by poor graft survival and limited localisation at the injury site. Here, we developed an injectable hydrogel-based delivery system (HGIL13) composed of IL-13-loaded poly(lactic-co-glycolic acid) (PLGA) microparticles embedded in a photocrosslinkable gelatin methacrylate (GelMA) matrix, enabling sustained and localised IL-13 release. HGIL13 achieved IL-13 release for up to six weeks and significantly reduced lipopolysaccharide (LPS)-induced inflammation in BV2 microglia in vitro. In a mouse contusion SCI model, HGIL13 enhanced functional recovery, reduced lesion volume, and decreased demyelinated area. Using the HexbtdTomato mouse we show that HGIL13 modulated the neuroimmune response by decreasing resident microglia density, downregulating CD86 expression, and upregulating Arginase-1 in both microglia and infiltrating monocyte-derived macrophages. RT-qPCR and RNA-seq analyses confirmed sustained immunomodulation over 28 days and indicated early reduction of activated microglia at 7 days post-injury as a key therapeutic mechanism. This study presents a safe, effective, and translatable strategy for localised cytokine delivery, demonstrating strong potential for immunomodulation and improved functional recovery following SCI.